Full-length cloning, sequence analysis and expression detection of the β-tubulin gene from the Chinese gall aphid (Schlechtendalia chinensis) - Ping Liu (Nature Portfolio, 2017)
Abstract Some insect galls are formed on sumac plants by certain aphid species and have been used for medicinal and chemical purposes as they are rich in tannins. The most prominent species among gall aphids in China is Schlechtendalia chinensis, which formed horn-shaped galls on the winged rachis of Rhus chinensis. S. chinensis has a complex life cycle, with a switch of hosts between R. chinensis and certain mosses, and a switch of sexual and asexual reproduction (cyclical parthenogenesis). We have cloned a full-length cDNA of the β-tubulin gene from S. chinensis, using qPCR and RACE. This cDNA has 1606 base pairs with a 251 bp 5′-untranslated region (5′-UTR) and a 15 bp 3′-untranslated region (3′-UTR). The gene encodes a protein with 376 amino acids residues. The expression levels of the β-tubulin gene in S. chinensis were investigated among fundatrigeniae and overwintering larvae rearing under either natural conditions, or at 7.5 °C and 18 °C. No significant differences (P > 0.01) in gene expression levels were found in insects under these conditions. It is indicates that the β-tubulin gene is highly conserved and then it may be used as a reference for further research in gene expression and reproduction determination in this important aphid.